THE EFFECT OF AUDIO VISUAL MEDIA ON SCIENCE LEARNING OUTCOMES IN GRADE IV STUDENTS OF UPTD STATE ELEMENTARY SCHOOL 122383 PEMATANG SIANTAR - Astri Sihaloho; Cindi Septia Br Tarigan; Nova Erawati Sidabalok (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to analyze the influence of audio visual media on science learning outcomes in fourth grade students of UPTD SD Negeri 122383 Pematang Siantar. This type of research applies quantitative by using the experimental method (Pre-experimental) with a one group pretest-posttest design held at UPTD SD Negeri 122383 Pematang Siantar This research was given to fourth-grade students with a population and sample of 29 students. The research instrument was in the form of multiple-choice test. Data processing ultilized the assistance of Microsoft Excel and IBM SPSS Statistic 26 application programs. The pretest results were 55.172 and the posttest results were 86.206. Referring to the results of the research analysis, the t-test results obtained with a t-count value > t-table or 17.797 > 2.048 and a significance level (2-tailed) < 0.05. This shows that the significant value (2-tailed) = 0.000 < 0.05 which means Ho is rejected and Ha is accepted. So it can be  concluded that there is an influence of audio-visual media on science learning outcomes in fourth-grade students at the UPTD SD Negeri 122383 Pematang Siantar. Statistical analysis shows a strong correlation (r=0.779) with the contribution of audio-visual media as seen from the R Square of 60.7%. The regression equation Y=61.986+0.438X shows that every 1% increase in audio-visual media increases learning outcomes 0.438.